Pemanfaatan Winhisab Dalam Menentukan Waktu Salat - Hasrian Rudi Setiawan; Arwin Juli Rakhmadi (University of Muhammadiyah Sumatera Utara, 2019)
Salat is a provision fardu (pillars of Islam) that have been determined time for those who believe. Both al-Qur'an and as-sunnah (hadith) have set the times of the prayer. From a number of methods and procedures for arranging the prayer time schedule is to use astronomical software called Winhisab compiled by the Indonesian Ministry of Religion. Utilization of this software is very easy and very helpful for Muslims in determining prayer times and in arranging prayer times for one year. Therefore this software is highly recommended to be studied and popularized in the Muslim community.